2014
DOI: 10.1177/0960327114532386
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel genes involved in gastric carcinogenesis by suppression subtractive hybridization

Abstract: Gastric cancer (GC) is one of the most common and life-threatening types of malignancies. Identification of the differentially expressed genes in GC is one of the best approaches for establishing new diagnostic and therapeutic targets. Furthermore, these investigations could advance our knowledge about molecular biology and the carcinogenesis of this cancer. To screen for the overexpressed genes in gastric adenocarcinoma, we performed suppression subtractive hybridization (SSH) on gastric adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Importantly, a relationship between RNase H2 and rNMPs incorporation with cancer is emerging. Screening of a cohort of patients with gastric cancers has recently revealed an association between the onset of gastric cancer and mutations in gene coding for the subunit B of RNase H2 (186). In parallel, a recent study has shown that RNase H2 can be also considered as a colorectal tumour suppressor gene (187).…”
Section: The Roles Of the Ber Pathway In Rna Processingmentioning
confidence: 99%
“…Importantly, a relationship between RNase H2 and rNMPs incorporation with cancer is emerging. Screening of a cohort of patients with gastric cancers has recently revealed an association between the onset of gastric cancer and mutations in gene coding for the subunit B of RNase H2 (186). In parallel, a recent study has shown that RNase H2 can be also considered as a colorectal tumour suppressor gene (187).…”
Section: The Roles Of the Ber Pathway In Rna Processingmentioning
confidence: 99%
“…This demonstration of genome instability has important implications for understanding the RNase H2 function in mammals as well as its contribution to disease avoidance. There have been no direct connections between RNase H2 mutation and cancer, although a recent study found that RNaseh2b was overexpressed in adenocarcinoma tissue from gastric cancer ( 55 ). It will be intriguing to further explore sequencing data generated from tumor samples to identify any links between RNase H2 deficiency, genome instability and tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…According to Cancer Facts and Figures, by the American Cancer Society, in 2015, 24,590 estimated new cases of gastric cancer will be diagnosed, and 10,720 deaths will occur in the United State [3]. Although, the incidence and mortality rate of gastric cancer have decreased dramatically in many nations, it still ranks 2 nd as the leading cause of cancer related deaths globally [4]. In Iran with about 8000 deaths annually, gastric cancer remains the first cause of cancer related death in both sexes [5].…”
mentioning
confidence: 99%